Note: I am assuming your second equation is:
x = 2y - 1
Answer:
The solution to the system of equations is:
Explanation:
Given the system of equations
2x+y=3
x = 2y - 1
solving the system of equations using the elimination method
Arrange equation variables for elimination
Multiply x-2y=-1 by2: 2x-4y=-2
subtracting the equations
now solve -5y = -5 for y
Divide both sides by -5
Simplify
For 2x+y=3 plug in y=1
subtract 1 from both sides
Simplify
Divide both sides by 2
Simplify
Therefore, the solution to the system of equations is: